Glass powders and reactive silicone binder: Interactions and application to additive manufacturing of bioactive glass-ceramic scaffolds. Issue 11 (1st August 2019) - Elsayed, Hamada; Picicco, Martiniano; Dasan, Arish; Kraxner, Jozef; Galusek, Dusan; Bernardo, Enrico
Abstract: A novel concept for the additive manufacturing of three-dimensional glass-ceramic scaffolds, to be used for tissue engineering applications, was based on fine glass powders mixed with a reactive binder, in the form of a commercial silicone. The powders consisted of 'silica-defective glass' specifically designed to react, upon firing in air, with the amorphous silica yielded by the binder. By silica incorporation, the glass was intended to reach the composition of an already known CaONa2 OB2 O3 SiO2 system. Silica from the binder provided up to 15 wt% of the total silica. With the same overall formulation, silicone-glass powder mixtures led to nearly the same phase assemblage formed by the reference system, crystallizing into wollastonite (CaSiO3 ) and Ca-borate (CaB2 O4 ). Samples from silicone-glass powder mixtures exhibited an excellent shape retention after firing, which was later exploited in highly porous reticulated scaffolds, obtained by means of direct ink writing (DIW).